Economic And Health Related Quality Of Life Evaluation Of Tuberculosis Patients In Yemen - Othman, Gamil Qasem (2011)
The study aims to assess the economic and the health related quality of life for tuberculosis patients in Yemen. A Cohort prospective study was carried out among pulmonary tuberculosis and extra pulmonary tuberculosis patients diagnosed and treated in a TB centers in Sana’a, the capital city of Yemen. Socio demographic, clinical and laboratory data and types of drug regimen used in treatment were collected from TB patients and medical records at the TB centers. Pharmacoeconomic methodology was applied to calculate direct and indirect costs. The patients were asked to complete DR-12 questionnaire. The patients was subjected to the questionnaire at onset of treatment, then after one month and finally repeated at the end of intensive phase of treatment.